Screening of red rice accessions for resistance to brown planthopper Nilaparvata lugens Stal. - Pati, Prajna; Jena, Mayabini; Annamalai, M; Behera, Santosh Kumar; S, Raghu; Bhattacharya, Swarnali; Sanghamitra, P; Pandi G, Guru Prasanna; K, Sankari Meena (ORYZA-An International Journal of Rice, 2018)
Red rice is the reservoir of large amount of phytochemicals such as carotenoids, phenolics, alkaloids, nitrogen and organosulfur containing compounds, possesses antioxidant properties, richer source of protein, zinc and have nutritive and medicinal value. Present study examines the utility of red rice accessions for their resistance against Brown planthopper with their mechanism of resistance. A total of 215 red rice accessions along with susceptible check TN1, resistance checks PTB-33 and Salkathi were evaluated under greenhouse conditions at the ICAR - National Rice Research Institute (NRRI), Cuttack. Accessions were screened using standard seed box screening technique followed by replicated screening for the confirmation of resistant reaction. Out of 215 red rice accessions, only four found to be highly resistant (score-1), eleven accessions shown resistant reaction (Score-3) and 13 accessions were moderately resistant (Score-5) to BPH. Mechanism of resistance was studied in these resistant accessions through the methods nymphal preference to plant. Among the resistant accessions, matameher and Manipuri black showed least nymphal preference when compared to control. Resistant genotypes identified and confirmed in the present study could be added as new resistant donors and utilized in resistance breeding programme against BPH in rice.